PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA (BEI) 2016 - 2019 - Dimas Ahmad Hernawan; Fauzan Fauzan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Stock prices are one of the main components of the capital market that are most important and attractive to investors because they are predicted to provide a favorable rate of return. Companies that are able to increase stock prices will be in demand by investors. Company performance is one of the important factors in determining stock prices. Research on stock prices is still very interesting to study, because it always gets different results. The purpose of this study is to analyze whether the Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA) dan Net Profit Margin (NPM) has an effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The population in this study were 150 food and beverages companies, the data used were annual financial reports published by the company. The sampling method used was purposive sampling method and obtained 12 sample companies for five years of observation (2016-2019) so that there were 60 samples. The data analysis tool uses multiple linear regression analysis. Based on the results of the study, it can be concluded that Current Ratio (CR) and Debt to Equity Ratio (DER) have negative and significant effect on stock prices, Net Profit Margin (NPM) has positive and significant effect on stock prices, while Return On Assets (ROA) has no effect on stock prices.